2015
DOI: 10.1016/j.psi.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening suicide prevention networks: Interorganizational collaboration and tie strength

Abstract: a b s t r a c tOne explanation for the continued high rates of suicide in the United States may be insufficient coordination between organizations involved in prevention. Therefore, the factors that promote interorganizational collaboration should be identified and fostered. Surveys were administered to 37 organizations involved in suicide prevention in one Colorado community to: (1) assess the nature of collaboration and (2) identify relationship strength indicators associated with different types of collabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…In consequence, it is particularly relevant in studies of community psychology and in psychosocial interventions. As we show in this monograph, networks allow to detect patterns of collaboration that are not perceived intuitively (Todd et al, 2015), serve to examine the mutual influence of individual community organizations and networks of interorganizational collaboration (Faust et al, 2015;Menger et al, 2015;Rana & Allen, 2015), facilitate the dissemination of evidencebased practices among professionals of the intervention , and are a tool for intervention by themselves (Corlew et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In consequence, it is particularly relevant in studies of community psychology and in psychosocial interventions. As we show in this monograph, networks allow to detect patterns of collaboration that are not perceived intuitively (Todd et al, 2015), serve to examine the mutual influence of individual community organizations and networks of interorganizational collaboration (Faust et al, 2015;Menger et al, 2015;Rana & Allen, 2015), facilitate the dissemination of evidencebased practices among professionals of the intervention , and are a tool for intervention by themselves (Corlew et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Two important issues in this regard are the core-periphery structure, and interaction of individual organizations with the whole network. On the one hand, the existence of a small core of organizations densely connected to each other seems to be fundamental to the proper functioning of coalitions (Faust et al, 2015;Menger et al, 2015;Rana & Allen, 2015). On the other hand, links with a network of entities allow individual community organizations to improve their effectiveness (Faust et al, 2015), although that makes the organization is also more exposed to the influence of political and social norms of the network (Rana & Allen, 2015).…”
Section: Interorganizational Network and Community Coalitionsmentioning
confidence: 99%
“…Community suicide prevention networks rely on organizations working together to implement a suicide prevention plan. Organizations tend to be more connected around information and resource sharing and less collaborative around infrastructure and training, so this may need good negotiation and diplomacy skills by the practitioner (Menger et al 2015). It has also been suggested that the best way an organization can improve its collaboration with other organizations is through regular communication and developing trusting relationships (Menger et al 2015).…”
Section: Communicationmentioning
confidence: 99%
“…Organizations tend to be more connected around information and resource sharing and less collaborative around infrastructure and training, so this may need good negotiation and diplomacy skills by the practitioner (Menger et al 2015). It has also been suggested that the best way an organization can improve its collaboration with other organizations is through regular communication and developing trusting relationships (Menger et al 2015). This could indicate the need for developing collaborative networks that meet on a regular basis to provide an ongoing identification of the communities needs and evaluate the strategies being implemented.…”
Section: Communicationmentioning
confidence: 99%
“…The standardisation of shareddecision making has a positive influence on respecting patient wishes 51 . Although support for communication and leadership is often mentioned as an important factor to improve inter-organisational collaboration in other healthcare domains, the need for structural aspects of collaboration is not explicitly addressed [52][53][54][55] . As such, our findings may reflect the particular nature of inter-organisational collaboration in palliative care.…”
Section: Priorities To Stimulate Inter-organisational Collaborationmentioning
confidence: 99%